Waste management improvement with software application at Wringinsongo Village, Tumpang Regency, Malang - Dimas Wahyu Wibowo; Muhammad Shulhan Khairy; Muhammad Akhlis Rizza; Annisa Fitriana; Padma Adriana Sari (University of Merdeka Malang, 2024)
Wringinsongo Village, Tumpang Subdistrict, Malang Regency maintains a clean environment through environmentally friendly waste management. One of Wringinsongo's BUMDes (Village-Owned Enterprises) is the Waste Bank, which uses waste as a potential sector. It needs to get special attention related to its governance because the recording is still less effective and there are often calculation errors caused by the recording system using paper. Based on these conditions, it is necessary to develop an application to help record transaction activities at the Waste Bank. The Wringinsongo Village Waste Bank application can be accessed on both the web platform and Android mobile devices, based on the ease of access to the system by village managers and officials. After developing the application, socialization, and training were conducted to the Waste Bank manager and village officials to provide information on how to use the application. After three months of use, feedback was taken to get responses related to the use of the application. The result is that BUMDes managers find it easy to record and obtain accurate and faster calculation results.